O SILÊNCIO DAS GERAIS: O nascimento tardio e a lenta consolidação dos jornais mineiros - Mendes, Jairo Faria (2007)
This paper analyses the facts that were responsible for the delay in the appearance and development of newspapers in the state of Minas Gerais during its main stages: political-discourse press, informative press and the greater print media. Despite its political and economical importance during the XVII and XIX centuries, the State of Minas Gerais saw its press play a secondary role in the country. It was the sixth province to have newspapers, a step behind the states of Rio de Janeiro, Bahia, Pernambuco, Pará and Maranhão. To understand what made Minas Gerais remain in that position, it was necessary to learn deeply about its particularities. The research demonstrated that the suppression applied against the Inconfidência Mineira (Minas Conspiracy), the migratory movements and the social and economic changes the province underwent during the XIX century were responsible for the delay in the establishment of the state s newspapers. The typical lifestyle of the state s native people, called mineiridade , also contributed to the fact.(AU)